Digital Readiness and Innovation Behavior: The Role of Technology Adoption and Organizational Agility in Manufacturing Firms - Rahmadani, Eki Prafitri; Maelani, Susi; Putri, Mei Candra; Pratiwi, Ardila (Lentera Ilmu Nusantara, 2025)
This study aims to examine the influence of digital readiness on innovation behavior in manufacturing companies in West Java, considering the role of technology adoption as a mediating variable and organizational agility as a moderating variable. Using a quantitative approach and the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, the findings reveal that digital readiness positively influences innovation behavior directly and is also associated with higher levels of technology adoption within organizations. However, technology adoption is not found to significantly mediate the relationship between digital readiness and innovation behavior. On the other hand, organizational agility strengthens this relationship, indicating that organizations responsive to change are better equipped to translate digital readiness into innovative actions. Theoretically, these findings extend the literature on digital transformation and innovation management by demonstrating that the integration of digital readiness with organizational agility provides a stronger explanatory framework for how firms achieve innovation outcomes in dynamic environments. These findings imply that in fostering a sustainable culture of innovation, companies should not only focus on enhancing digital readiness and technology adoption capabilities but also prioritize strengthening organizational agility to effectively respond to dynamic changes.